WATER CONSERVATION: A GLOBAL NEED - Verma, A.; Shrivastava, P; Nahatkar, S B (International Journal of Research -GRANTHAALAYAH, 2020)
Water is the lifeline of any nation’s richness and development. We should conserve water for future generations as it can be big trouble for the country. Since ancient times, the region of high prosperity for water resources was considered a subcontinent, but today like other countries of the world, India's water crisis problem, is vivid. India is the world's largest groundwater extractor, pumping about twenty-five percent of the world's groundwater use annually. Five of the world's 20 largest cities in water stress are in India, with Delhi in second place. India has 16% of the world's population and only 4% of the world's water resources, which are rapidly reducing. Daily struggles for the fetching water, mismanagement of wastewater, improper sanitation are common features affecting human health and the economy of the nation indirectly. The situation calls for widespread intrusion in the management of this rapidly growing problem. The water crisis will not go away on its own. On the contrary, it will deteriorate until we respond as a global community and use water responsibly. Therefore, before it is too late, let us all pledge to use water wool as individuals, families, communities, companies, and institutions. Intelligence is not in elegance, but preservation so that our future generations can enjoy the joy and touch of water.